How Regulation and Enforcement of Competition Affects ICT Productivity : Evidence from Matched Regulatory-Production Surveys in Peru’s ICT Sector - Arayavechkit, Tanida (World Bank, Washington, DC, 2022)
How the enforcement of competition regulation of information and communications technology affects growth depends on how well firms adapt to competitive pressure. This paper tests this empirically using Peruvian firm-level data matched to a compilation of information and communications technology regulations and competition enforcement cases over 10 years. Based on the theoretical dispersion in markups, the paper shows that by increasing productivity, leaders in a market can avoid the effects of competition while maintaining market share. However, much depends on the regulatory structure, which affects productive firms differently depending on how long they have been in business. Highly productive older firms translate regulations that make processes more complex (such as raising quality standards) into more productivity; productive younger firms benefit more from simplifying rules that facilitate competition through lower entry barriers and improved operating conditions. This feature is consistent across different segments of the information and communications technology sector.